Effects Of Tui Na Massage On Stunted Toddlers Aged 3-4 Years - Ayuningtyas, Nova; Lestari, Gangsar Indah; Sumiyati, Sumiyati (JKM (Jurnal Kebidanan Malahayati), 2024)
Background: Stunting is a form of chronic malnutrition resulting from inadequate nutrient intake over a prolonged period, often due to insufficient feeding that fails to meet nutritional requirements. The prevalence of stunting among children under the age of five in Indonesia was 36.4% in 2015. However, the 2023 health profile research in Lampung Province reported a prevalence of 4.0%, and in the working area of the Purwosari Health Center, the incidence of stunting was 5.7%. A preliminary survey conducted by researchers found 14 stunted toddlers in the Purwosari Health Center working area.Aim: This study aimed to investigate the effect of Tui Na Massage on stunted toddlers aged 3-4 years in Purwosari North Metro Health Center's working area.Methods: This study utilized quantitative research with a quasi-experimental method and a one-group pretest-posttest design approach. The target population was 14 stunted toddlers aged 3-4 years within the Purwosari Health Center's working area in Metro City. The sample also included 14 respondents, with the sampling technique using total sampling. Data collection methods comprised questionnaires, scales, and stature meters. Data analysis involved univariate analysis using mean values and bivariate analysis using paired sample t-tests.Results: The research involved 14 participants who were measured before and after the Tui Na massage. Before the massage, the average body weight was 12.99 kg, and the average height was 88.07 cm. After the massage, the average body weight increased to 13.36 kg, and the average height increased to 89.07 cm. The average increase in body weight was 0.37 kg (370 grams), and height was 1.00 cm. The paired samples test yielded a p-value of 0.000 (p<0.05), indicating a statistically significant difference.Conclusion: Tui Na massage has an effect on increasing body weight and height in toddlers aged 3-4 years in Purwosari Health Center's Working Area.Recommendation: Suggestions for healthcare workers include providing Tui Na Massage as an alternative therapy to support the growth of stunted toddlers and to prevent stunting in children.Keywords : Toddlers, Stunting, Tui Na Massage